Chemotherapy-associated paronychia treated with 2% povidone–iodine: a series of cases - Capriotti, Kara (Cancer Manag Res, 2017)
BACKGROUND: Nail changes are known to occur during the use of chemotherapy for a variety of malignancies, particularly those treated with taxanes and EGFR inhibitors. There are currently no actively recruiting prospective clinical trials investigating potential treatments. There are also no US Food and Drug Administration-approved medical treatments for chemotherapy-associated paronychia and no consensus on the best way to treat these common chemotherapy-induced events. METHODS: A retrospective review of all cases presenting to a single dermatology private practice from June 2016 to January 2017 identified nine patients with chemotherapy-associated paronychia seeking treatment. Each patient was prescribed a topical solution comprised of 2% povidone–iodine in a dimethylsulfoxide vehicle that was prepared by a licensed compounding pharmacy. Patients were seen at 3 week and 6 week follow-up visits. RESULTS: All 9/9 patients demonstrated complete or partial resolution. The number of nails involved for each patient ranged from 4–12. There were a total of 58 nails affected in the case series, and 44/58 (76%) resolved overall. The treatment was well tolerated. CONCLUSION: The topical povidone–iodine/dimethylsufoxide solution described is very effective in alleviating the signs and symptoms of paronychia associated with chemotherapy. This novel combination warrants further investigation in randomized, controlled trials to further elucidate its clinical utility.